2022
DOI: 10.52970/grfm.v2i1.97
|View full text |Cite
|
Sign up to set email alerts
|

Current Ratio, Return on Asset, and Debt-to-Equity-Ratio on Stock-Price of Sector Property and Real Estate

Abstract: The purposes of this study are: to analyze the current ratio (CR), return on assets (ROA), and debt to equity ratio (DER) both partially and simultaneously affect the stock price of companies listed on the Indonesia Stock Exchange (IDX) in the property sector and real estate. This study uses 31 companies to sample the 55 property and real estate sector from 2017-2021. The sampling technique was carried out using the purposive sampling method. The test used in this study was multiple regression analysis with t-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
1
3
1
Order By: Relevance
“…High liquidity levels influence investor interest in the company. However, this result contrasts with Tangngisalu (2022) research, showing a negative and significant relationship between CR JAMEELA 2,1 and stock prices. This discrepancy may be influenced by industry characteristics and other market factors.…”
Section: Introductioncontrasting
confidence: 99%
See 2 more Smart Citations
“…High liquidity levels influence investor interest in the company. However, this result contrasts with Tangngisalu (2022) research, showing a negative and significant relationship between CR JAMEELA 2,1 and stock prices. This discrepancy may be influenced by industry characteristics and other market factors.…”
Section: Introductioncontrasting
confidence: 99%
“…If the company's performance and prospects are good, it can be expected that the future value of the company will also be good, impacting the stock price (Sihotang & Mekel, 2015). In line with Tangngisalu (2022) and Sondakh, Saerang, and Samadi (2019) research, ROA has an influence on stock prices.…”
Section: Signaling Theorysupporting
confidence: 65%
See 1 more Smart Citation
“…This category is based on the generally accepted state of the company's financial health. A 5% or better ROA is typically considered a good ratio, while 20% or better is considered great [48]. A 15-20% ROE is generally considered good [49].…”
Section: Resultsmentioning
confidence: 99%
“…Reliability between 0.6 and 0.7 is acceptable provided that the other indicators of construct validity are valid. Goodness of Fit Indices (GOFI) measurements can be divided into three groups: absolute fit measures (Goodness of Fit Index (GFI), Expected Cross Validation Index (ECVI) and Root Mean Square Error of Approximation (RMSEA), incremental fit measures Tucker-Lewis Index (TLI), Normed Fit Index (NFI), Adjusted Goodness of Fit Index (AGFI), Incremental Fit Index (IFI), Comparative Fit Index (CFI), and parsimony fit measures Parsimony Normed of Fit Index (PNFI), and Akaike Information Criterion (AIC) (Allo et al, 2021;Handayani et al, 2020;Ilyas et al, 2020;Kartini et al, 2021;Malikah, 2021;Tangngisalu, 2022). Then it can be concluded that the questionnaire is reliable so that it is suitable for use in research.…”
Section: B Reliability Testmentioning
confidence: 99%